Statistical Analysis of Data From Electronic Component Lifetests (A Tutorial Paper) - J. Møltoft (Active and Passive Electronic Components)
Methods of statistically analysing data from electronic component lifetests are discussed. Particular emphasis is given to analysis techniques using the assumptions of constant hazard rate (Exponential distribution), the Weibull distribution and mixed Weibull distributions. The methods used for analysing Weibull data when the data itself is non-uniform due to both removal of test samples during test and also the non-continuance of surveillance of components under test are discussed. Attention is finally given to the effect of two or more failure mechanisms which can produce S-shaped patterns when data is plotted on Weibull Graph paper.